Analisis Sentimen Evaluasi Terhadap Pengajaran Dosen di Perguruan Tinggi Menggunakan Metode LSTM - Muhammad Afrizal Amrustian; Widi Widayat; Arif Muhammad Wirawan (STMIK Budi Darma, 2022)
Education in Indonesia is divided into several levels, from elementary education to university education. At the university education level, lecturers are asked to not only teach material but also emphasize to students that students have an important role for the future. Due the students are considered as adults to make the decisions and take a responsibility for those decisions. During a pandemic, teaching activities are carried out online, in order the teaching activities run well, the evaluation from students is needed. Considering that students are one of the important elements in university education. In this study, sentiment analysis was carried out on the evaluation of teaching by students. The data used in this study amounted to 2280 data with the number of words in the evaluation text ranging from 3 to 50 words. The LSTM method is the method used in this study, and the results of the accuracy of using the LSTM method are 91.08%. With the analysis carried out, lecturers can improve their teaching methods based on the results of the evaluation analysis.